The repertoire of epithelial morphogenesis on display: Progressive elaboration of Drosophila egg structure. (December 2017) - Duhart, Juan Carlos; Parsons, Travis T.; Raftery, Laurel A.
Abstract: Epithelial structures are foundational for tissue organization in all metazoans. Sheets of epithelial cells form lateral adhesive junctions and acquire apico-basal polarity perpendicular to the surface of the sheet. Genetic analyses in the insect model, Drosophila melanogaster, have greatly advanced our understanding of how epithelial organization is established, and how it is modulated during tissue morphogenesis. Major insights into collective cell migrations have come from analyses of morphogenetic movements within the adult follicular epithelium that cooperates with female germ cells to build a mature egg. Epithelial follicle cells progress through tightly choreographed phases of proliferation, patterning, reorganization and migrations, before they differentiate to form the elaborate structures of the eggshell. Distinct structural domains are organized by differential adhesion, within which lateral junctions are remodeled to further shape the organized epithelia. During collective cell migrations, adhesive interactions mediate supracellular organization of planar polarized macromolecules, and facilitate crawling over the basement membrane or traction against adjacent cell surfaces. Comparative studies with other insects are revealing the diversification of morphogenetic movements for elaboration of epithelial structures. This review surveys the repertoire of follicle cell morphogenesis, to highlight the coordination of epithelial plasticity with progressive differentiation of a secretory epithelium. Technological advances will keep this tissue at the leading edge for interrogating the precise spatiotemporal regulation of normal epithelial reorganization events, and provide a framework for understanding pathological tissue dysplasia. Highlights: The follicular epithelia of Drosophila ovary are an accessible genetic model to study epithelial morphogenesis. Collective cell migration, reorganization into distinct domains, and tubulogenesis occur in succession during morphogenesis. Recent data on lateral adhesion junction remodeling are highlighted for each of these events. Differentiation into a secretory epithelium completes the formation of the elaborate eggshell that surrounds the mature egg.